The Best of What We Are : Reflections on the Nicaraguan Revolution - Brentlinger, John (University of Massachusetts Press, EE UU, 1995)
John Brentlinger made six trips to Nicaragua, both before and after the defeat of the Sandinista Party. Combining the insights of a philosopher with the experiences of a participant-observer, he interprets the Sandinista period as a people's struggle for self-realization in work, culture, politics, and community. The book alternates between journal and essay chapters, weaving descriptions of personal experiences together with interviews and analysis.